2014
DOI: 10.1007/s10107-014-0763-3
|View full text |Cite
|
Sign up to set email alerts
|

On the augmented Lagrangian dual for integer programming

Abstract: We consider the augmented Lagrangian dual for integer programming, and provide a primal characterization of the resulting bound. As a corollary, we obtain proof that the augmented Lagrangian is a strong dual for integer programming. We are able to show that the penalty parameter applied to the augmented Lagrangian term may be placed at a fixed, large value and still obtain strong duality for pure integer programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In Boland and Eberhard (), and later in Feizollahi et al. (), it has been observed that a zero duality gap is achievable for dual problems based on an augmented Lagrangian in MIP problems.…”
Section: Technical Backgroundmentioning
confidence: 95%
See 4 more Smart Citations
“…In Boland and Eberhard (), and later in Feizollahi et al. (), it has been observed that a zero duality gap is achievable for dual problems based on an augmented Lagrangian in MIP problems.…”
Section: Technical Backgroundmentioning
confidence: 95%
“…Recent results have shown that, for penalty functions satisfying some slight conditions, the augmented Lagrangian dual is capable of asymptotically achieving zero duality gap when the penalty term coefficient ρ is allowed to go to infinity (Boland and Eberhard, , Proposition 3; Feizollahi et al., , Proposition 2). However, despite the theoretical relevance of this observation, it is not practically meaningful to deal with large‐valued penalty parameters, in large part due to the associated numerical issues that arise.…”
Section: Technical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations